An evaluation of "on-line" banking web sites in South Africa to determine essential design criteria - Palmer, Lydia (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
The use of the Web to carry out business on the Internet has become a viable option in all business sectors, and Internet banking in South Africa is no exception. The nature of business on the Internet in South Africa and the World is investigated. The extent of Internet banking in South Africa is ascertained and the expectations and perceived problems of online bankers are discussed. The importance of Human Computer Interface and Web Interface Design for successful business is promoted with a discussion of their guidelines and principles. Web Evaluation techniques and Tools are assessed and The "Gartner" Web evaluation tool is selected to evaluate the three bank Web sites. The results of the evaluation indicate that there are several generally well implemented design criteria used by all of the banks while some criteria are not implemented at all. Each bank is discussed individually to identify strong and weak features of their Web site design. Essential aspects of Web design have been proposed for inclusion during the design of "online" Banking Web sites.
Keywords: Banks and banking -- South Africa; Banks and banking -- Customer services -- South Africa; Home banking services -- South Africa; Electronic funds transfers -- South Africa; Web sites -- Design